НЕСТАНДАРТНІ ЗАВДАННЯ ЯК ЗАСІБ АКТИВІЗАЦІЇ УЧІННЯ МОЛОДШИХ ШКОЛЯРІВ (Педагогіка вищої та середньої школи, 2004)
The peculiarity of using the utraditional tasks to activate junior pupils studying in innovation teaching technology are examined in the article.